The GluN2B-Selective Antagonist Ro 25-6981 Is Effective against PTZ-Induced Seizures and Safe for Further Development in Infantile Rats - Mareš, Pavel; Kozlová, Lucie; Mikulecká, Anna; Kubová, Hana (Pharmaceutics, 2021)
The GluN2B subunit of NMDA receptors represents a perspective therapeutic target in various CNS pathologies, including epilepsy. Because of its predominant expression in the immature brain, selective GluN2B antagonists are expected to be more effective early in postnatal development. The aim of this study was to identify age-dependent differences in the anticonvulsant activity of the GluN2B-selective antagonist Ro 25-6981 and assess the safety of this drug for the developing brain. Anticonvulsant activity of Ro 25-6981 (1, 3, and 10 mg/kg) was tested in a pentylenetetrazol (PTZ) model in infantile (12-day-old, P12) and juvenile (25-day-old, P25) rats. Ro 25-6981 (1 or 3 mg/kg/day) was administered from P7 till P11 to assess safety for the developing brain. Animals were then tested repeatedly in a battery of behavioral tests focusing on sensorimotor development, cognition, and emotionality till adulthood. Effects of early exposure to Ro 25-6981 on later seizure susceptibility were tested in the PTZ model. Ro 25-6981 was effective against PTZ-induced seizures in infantile rats, specifically suppressing the tonic phase of the generalized tonic-clonic seizures, but it failed in juveniles. Neither sensorimotor development nor cognitive abilities and emotionality were affected by early-life exposure to Ro 25-6981. Treatment cessation did not affect later seizure susceptibility. Our data are in line with the maturational gradient of the GluN2B-subunit of NMDA receptors and demonstrate developmental differences in the anti-seizure activity of the GluN2B-selective antagonist and its safety for the developing brain.
Keywords: Ro 25-6981; GluN2B-selective antagonist; motor performance; immature rats; memory; development; anti-seizure effects